2019
DOI: 10.1111/jam.14343
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and virulence genes in nisin‐resistantEnterococcus faecalisisolated from raw buffalo milk modulate the innate functions of rat macrophages

Abstract: Aims: To elucidate the antibiotic resistance and virulence genes of nisinresistant Enterococcus faecalis isolated from raw buffalo milk and to study the effect of nisin-sensitive and -resistant E. faecalis on the innate immunity of rats. Methods and Results: Slanetz-Bartley agar plates containing nisin were used to isolate nisin-resistant E. faecalis. The virulence factors were ascertained using quantitative real-time polymerase chain reaction. Cell viability, phagocytosis, intracellular survival and enzyme as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…The mechanisms by which the bacteria survived in the phagosomes merit further study, as the surviving macrophage population had an elevated level of internal ROS (Figure 2b). The present findings agree with those of Kumar et al (2019) in terms of intracellular survival of nisin‐resistant E . faecalis within macrophages.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The mechanisms by which the bacteria survived in the phagosomes merit further study, as the surviving macrophage population had an elevated level of internal ROS (Figure 2b). The present findings agree with those of Kumar et al (2019) in terms of intracellular survival of nisin‐resistant E . faecalis within macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…The present findings agree with those of Kumar et al (2019) in terms of intracellular survival of nisin-resistant E. faecalis within macrophages. However, in their study, diminished ROS activity was suggested as the mechanism of bacterial survival, whereas in the present study, the internal ROS activity was elevated in the macrophage after 48 h (Kumar et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Approximately, 80–90% of enterococcal infections are caused by Enterococcus faecalis , a commensal bacterium inhabiting the gastrointestinal tracts of humans [ 1 , 4 ]. E. faecalis has developed resistance to commonly used antibiotics such as vancomycin, aminoglycosides, daptomycin, tetracycline, linezolid, and quinolones [ 5 , 6 ]. In concert with antibiotic resistance, E. faecalis has also been reported to possess a reservoir of virulence genes and it can transfer these genes to other pathogenic bacteria [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that HPrK/P plays an important role in the fitness of antibiotic resistant E. faecalis . Therefore, the present study is aimed at identifying active-site targeted HPrK/P inhibitors against nisin-resistant E. faecalis that showed resistance to antibiotics [ 5 ]. Nisin is a class I bacteriocin that is used as a preservative for many food products.…”
Section: Introductionmentioning
confidence: 99%